Influence of the collection season on production, size, and chemical composition of bee pollen produced by apis mellifera l. - Negrao, Adriana Fava [UNESP]; Barreto, Lidia Maria Ruv Carelli; Orsi, Ricardo de Oliveira [UNESP] (Research Inst Pomology Floriculture, Div Apiculture, 2014)
The aim of our study was to investigate how the collection period affects and influences the production, chemical composition, and size of bee pollen loads (0.5, 1.0, 2.0, greater than 2.0 mm). The results showed there was a predominance of pollen loads with a diameter greater than 2.0 mm in all the production seasons. For all the seasons, there were no differences in protein content between the particle sizes. But when comparing 0.5 mm during the different periods, there were significant differences; the highest value was found during the winter (24.39 +/- 3.7%). As far as lipids and crude fiber are concerned, we obtained differences between the same granulometry sizes for the spring and summer seasons. As for ashes, the results showed differences between different particle sizes for the summer and autumn seasons. Our results have shown that regardless of pollen particle size, its quality was not altered, suggesting that smaller loads can be commercially used by containing nutritional quality or else be used by beekeepers as a supplement during periods of food scarcity.
Keywords: Bee pollen; Chemical composition; Pollen particle size; Protein content; Seasonal variation